Liquid crystal-templated chiral nanomaterials: from chiral plasmonics to circularly polarized luminescence - Zhang, Xuan; Xu, Yiyi; Valenzuela, Cristian; Zhang, Xinfang; Wang, Ling; Feng, Wei; Li, Quan (Light, science & applications, 2022)
Chiral nanomaterials with intrinsic chirality or spatial asymmetry at the nanoscale are currently in the limelight of both fundamental research and diverse important technological applications due to their unprecedented physicochemical characteristics such as intense light-matter interactions, enhanced circular dichroism, and strong circularly polarized luminescence. Herein, we provide a comprehensive overview of the state-of-the-art advances in liquid crystal-templated chiral nanomaterials. The chiroptical properties of chiral nanomaterials are touched, and their fundamental design principles and bottom-up synthesis strategies are discussed. Different chiral functional nanomaterials based on liquid-crystalline soft templates, including chiral plasmonic nanomaterials and chiral luminescent nanomaterials, are systematically introduced, and their underlying mechanisms, properties, and potential applications are emphasized. This review concludes with a perspective on the emerging applications, challenges, and future opportunities of such fascinating chiral nanomaterials. This review can not only deepen our understanding of the fundamentals of soft-matter chirality, but also shine light on the development of advanced chiral functional nanomaterials toward their versatile applications in optics, biology, catalysis, electronics, and beyond. This review focuses on liquid crystal-templated chiral functional nanomaterials, including chiral plasmonic nanomaterials and chiral luminescent nanomaterials, introducing their underlying mechanisms, chiroptical properties, and potential applications.